ISSP 1994 - Family and changing gender roles II: Sweden - Edlund, Jonas; Svallfors, Stefan; Sundström, Eva (Umeå University, 2011)
This is the Swedish part of the 1994 'International Social Survey Program' (ISSP), and this is the second time ISSP focuses on the significance of family and changing gender roles.

Questions cover the respondents attitude to employment of women and the role distribution of man and woman. Other questions deal with how much women should work outside the home during various stages of child raising. The respondents also gave their opinions on different aspects of marriage, divorce and having children. The respondents reported if their own mother worked during their childhood and stated their present contacts with their mother. Other questions deal with personal divorces and earlier divorce of present partner. Married persons were asked if they lived together with their partner before marriage and all respondents were asked if they ever did live together with partner without being married. Furthermore the respondents had to give their opinions on: paid maternity leave; financial benefits for child care; right to free abortion; sexual relations before marriage; sexual relations under the age of 16; extra-marital sexual relations; and sexual relations between two adults of the same sex. People married or living as married were asked who earns more money and how they managed their income, if they kept their own money separate or if they pooled the money. They were also asked how they divide the work between man and woman when it comes to housework such as: laundry, small repairs, care for sick family members, shopping for groceries and decision what to have for dinner. All respondents that ever had children were asked about their own and partner´s extent of employment during various stages of cild raising. Socio-economic background information include: employment status; weekly working hours; occupation; employee or self-employed; supervisory function; work in private or public sector; trade union membership; education; years in school; income; marital status; spouse´s employment status, occupation and socio-economic classification; spouse employed or self-employed; family income; age and gender of other persons in household; party preference; self-classification of social class; religious affiliation and church attendance; gender; age; nationality.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 1994 investigating Family and Changing Gender Roles.

Detta är den första svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 1994 är ”Family and Changing Gender Roles”. Detta är andra gången studien genomförs på det här temat och har sedan genomförts ytterligare två gånger på samma tema (SND 0793, SND 0929).

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. I studien 1994 undersöks åsikter om familjeliv och könsroller.
ISSP 1994 - Åsikter om familjeliv och könsroller
Keywords: employment; anställning; children; barn; interpersonal relations; mellanmänsklig relation; housework; hushållsarbete; marriage; äktenskap; domestic responsibilities; hushållsansvar; child care; barnomsorg; family life; familjeliv; premarital sex; föräktenskaplig förbindelse; Sexual Behavior; Sexuellt beteende; families; familjer; households; hushåll; working mothers; förvärvsarbetande mödrar; married women workers; förvärvsarbetande gifta kvinnor; gender role; könsroll; CORS; CORS; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Gender and gender roles; Kön och könsroller; Family life and marriage; Familjeliv och äktenskap; Social Sciences; Samhällsvetenskap; Sociology; Sociologi